Respuesta :
Equations:
2x+y=1 ..............(1)
3x-y=-6...............(2)
The two equations have different slopes -2, 3, so there is a unique solution.
Add (1) & (2)
2x+3x = -5 => x=-1
Substitute x=-1
into (1) : 2(-1)+y=1 => y=3
into (2) : 3(-1)-y = -6 => y=3 checks.
=>
The solution is (-1,3).
Note: None of the above answer choices fit, so please check for typos.
2x+y=1 ..............(1)
3x-y=-6...............(2)
The two equations have different slopes -2, 3, so there is a unique solution.
Add (1) & (2)
2x+3x = -5 => x=-1
Substitute x=-1
into (1) : 2(-1)+y=1 => y=3
into (2) : 3(-1)-y = -6 => y=3 checks.
=>
The solution is (-1,3).
Note: None of the above answer choices fit, so please check for typos.
Answer: The required solution is (x, y) = (-1, 3).
Step-by-step explanation: We are given to find the solution to the following system of equations :
[tex]2x+y=1~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)\\\\3x-y=-6~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(ii)[/tex]
We will be using the method of Elimination to solve the given system.
Adding equations (i) and (ii), we get
[tex](2x+y)+(3x-y)=1+(-6)\\\\\Rightarrow 5x=-5\\\\\Rightarrow x=-\dfrac{5}{5}\\\\\Rightarrow x=-1.[/tex]
From equation (i), we get
[tex]2\times(-1)+y=1\\\\\Rightarrow -2+y=1\\\\\Rightarrow y=1+2\\\\\Rightarrow y=3.[/tex]
Thus, the required solution is (-1, 3).